Correlation analysis of sensory and scientific evaluation during the storage of oysters (Crassostrea gigas) - Jiyoung Shin; Junho Yang; Jisoo Han; Yeonhwa Park; Sanghwa Kang; Gangmi Nam; Seokwon Kang; Beom-Su Cho; Ji-Young Yang (Applied Food Research)
The freshness of oysters is challenging to assess, necessitating the development of a standard quality evaluation method. This study aimed to determine the correlation between sensory and scientific evaluations of oysters. We observed that the body was darkened, the adductor appeared light gray, and the boundary between the mantle and the body was blurred on day 5. On day eight of storage, the body exhibited a beige-like color, with the appearance of some stripes. The number of visible fibers decreased, and the adductor muscle appeared light gray and opaque. The color of the mantle became cloudy, and the boundary with the body was unclear. On day nine, the body was slightly swollen, and the fiber lines of the gills could not be distinguished. Moreover, the adductor appeared cloudy with a grayish hue. The mantle was blurred, with unclear boundaries. The oyster color became brighter as decay progressed, with an increase in red and yellow hues. The pH decreased from 6.15 to 5.61 from days 0 to 10. In the fresh state, the volatile basic nitrogen (VBN) level was 6.92; however, it increased to 52 after 10 days of storage, indicating spoilage. The total quality index method (QIM) score exhibited the highest positive correlation with VBN levels of 0.940, and a negative correlation with hardness at -0.939. This correlation was further confirmed, and the estimated spoilage period was found to be similar. These findings confirm a correlation between VBN levels and the total QMI, indicating that scientific evaluations can offer information on sensory quality.